التعرف الآلي على الأحرف العربية باستخراج سماتها البنيوية - أبو الشامات, روعة (Latakia University Journal -Engineering Sciences Series, 2016)
يقدم هذا البحث مساهمة جديدة في عملية تطوير خوارزمية فَعّالة تُحقق التعرف على الأحرف العربية لمعالجة صور المستندات النصية باستخدام الشبكات العصبونية التي أثبتت جدواها في حل العديد من المسائل المشابهة, وقد تضمن البحث العديد من الأفكار الجديدة، والخوارزميات, لمواجهة وحل التعقيد البالغ في النصوص العربية كما تم في سياق العمل تقديم دراسة مرجعية حول طرائق التعرف على الأنماط، والخوارزميات المستخدمة للتعرف على الكتابة باللغة العربية، بالإضافة إلى الاهتمام بعلم معالجة الصور مع التركيز على الشبكات العصبونية وخاصة شبكات هامينغ . اعتُمدَت طريقة استخراج السمات البنيوية للحرف المراد التعرف عليه في عملية التصنيف. تم التوصل في نهاية البحث إلى مجموعة من النتائج والاستنتاجات، بالإضافة إلى مقارنة أنواع مختلفة من الخطوط، وبأحجام متباينة، حيث كانت نسبة التعرف مرتفعة في أغلب الحالات، بينما انخفضت بشكل بسيط عند زيادة نسبة الضجيج, كما حُددت الحالات الخاصة الواجب التعامل معها أثناء التعرف على الأحرف العربية، وذلك ليتسنى أخذها بعين الاعتبار عند تقديم خوارزميات تعرف جديدة. This research presents new effective contribution of developing the algorithm of identifying and recognizing Arabic letters in the text document by using neural network which proved its strong ability in solving many similar issues. This research includes also many new ideas and algorithms to solve the extreme complexity of Arabic texts, and in the sequence of work an authoritative study has been set about the methods of identifying modes and algorithms of Arabic language. In addition, the study took care of images processing technology and concentrated on the neural networks (Hamming Networks) specifically. Extracting the structural features of the letter (which wanted for recognition)has been adopted during the classification process). At the end of this study a band of conclusions and results has been reached, as well as, the comparison between different kinds of fonts and different sizes of letters. Mostly, a high ratio of successful identification could be reached, the ratio has slightly decreased in the case of high noise. Special cases of recognition of Arabic letters have been classified to be taken into consideration during the introduction of the new algorithms.